2014
DOI: 10.1038/ncomms5914
|View full text |Cite
|
Sign up to set email alerts
|

Validation of climate model-inferred regional temperature change for late-glacial Europe

Abstract: Comparisons of climate model hindcasts with independent proxy data are essential for assessing model performance in non-analogue situations. However, standardized paleoclimate datasets for assessing the spatial pattern of past climatic change across continents are lacking for some of the most dynamic episodes of Earth's recent past. Here we present a new chironomid-based paleotemperature dataset designed to assess climate model hindcasts of regional summer temperature change in Europe during the late-glacial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
169
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 154 publications
(177 citation statements)
references
References 30 publications
7
169
1
Order By: Relevance
“…While several environmental factors were found to be significant in our study, temperature was found to explain the largest variation in chironomid assemblage data, as has been shown in the past (Walker et al 1991;Medeiros and Quinlan 2011;Heiri et al 2014). This is not surprising as summer temperatures directly affect chironomid lifecycle development (Danks 2004;Eggermont and Heiri 2012) and is therefore an 'appropriate' variable (Huntley 2012;Juggins 2013) to reconstruct using chironomids.…”
Section: Discussionsupporting
confidence: 61%
“…While several environmental factors were found to be significant in our study, temperature was found to explain the largest variation in chironomid assemblage data, as has been shown in the past (Walker et al 1991;Medeiros and Quinlan 2011;Heiri et al 2014). This is not surprising as summer temperatures directly affect chironomid lifecycle development (Danks 2004;Eggermont and Heiri 2012) and is therefore an 'appropriate' variable (Huntley 2012;Juggins 2013) to reconstruct using chironomids.…”
Section: Discussionsupporting
confidence: 61%
“…The cladoceran-based summer temperature reconstructions from central Poland (12.2-16.5°C) are similar to the cladoceran-based estimates for eastern Poland (11.5-14.5°C; Łukie Lake; Zawiska et al 2014) and to the chironomid-inferred summer temperature estimates for the mid-latitudes (50-55°N) of east and central-southern Europe (Heiri et al 2014). Additionally, the YD temperature values from central Poland studied here are very similar to the estimates from lowlands and mid-elevation (up to 700 m a.s.l.…”
Section: Cladoceran-inferred Temperature Reconstitution and Regional supporting
confidence: 53%
“…A variation of this stacking and splicing procedure has recently been used to produce Lateglacial summer temperature reconstructions for different parts of Europe (Heiri et al, 2014a). Here, we discuss the approach and assumptions associated with it in detail.…”
Section: Introductionmentioning
confidence: 99%